From 'Green Space' to Tradition: Tangible/Intangible Cultural Heritage Dichotomy, Cultural Landscape and Protecting Yedikule Vegetable Gardening as World Heritage - AYKAN BENTAHAR, BAHAR (KARE PUBL, 2019)
As rare living examples of Istanbul's long-standing vegetable gardening tradition dating from the Byzantine period, Yedikule vegetable gardens are located within the borders of the Historic Areas of Istanbul in the UNESCO World Heritage List. Surrounding the historic land walls, these vegetable gardens are on the agenda since 2013 with plans to transform them into parks and recreation areas. Although this may appear contradictory to the World Heritage status of the vegetable gardens at first glance, these gardens are considered to be 'green spaces' surrounding the land walls and do not have a protection status. Based on in-depth interviews with Yedikule vegetable gardeners, this article aims to discuss the steps that can be taken in the presence of the convention to address and protect the vegetable gardening tradition together with the land walls through a cultural landscape approach. The category of cultural landscapes that was created in 1992 has enabled the identification and protection of both tangible and intangible characteristics of an area as a World Heritage site. Yedikule vegetable gardening has been carried on with traditional methods and techniques for generations, and cultural landscape category offers an opportunity for its protection as an organically evolved continuing landscape, together with the land walls with which it has co-existed for centuries. Such a change will provide the possibility to generate national and international public opinion to sustain vegetable gardening tradition and to develop policies and projects to support gardeners as heritage bearers and involve them in the decision-making processes.
Keywords: World Heritage; cultural heritage; cultural landscape; UNESCO; Yedikule vegetable gardens; RIGHTS